Evidence of Mycobacterium bovis DNA in shared water sources at livestock–wildlife–human interfaces in KwaZulu-Natal, South Africa - Matthews, Megan C.; Cooke, Deborah M.; Kerr, Tanya J.; Loxton, Andre G.; Warren, Robin M.; Ghielmetti, Giovanni; Streicher, Elizabeth M.; Witte, Carmel S.; Miller, Michele A.; Goosen, Wynand J. (Frontiers in Veterinary Science, 2025)
The Mycobacterium tuberculosis complex (MTBC) including Mycobacterium bovis (M. bovis), which primarily affects animal hosts; however, it is also capable of causing zoonotic infections in humans. Direct contact with infected animals or their products is the primary mode of transmission. However, recent research suggests that M. bovis can be shed into the environment, potentially playing an under-recognized role in the pathogen’ spread. Further investigation into indirect transmission of M. bovis, employing a One Health approach, is necessary to evaluate its epidemiological significance. However, current methods are not optimized for identifying M. bovis in complex environmental samples. Nevertheless, in a recent study, a combination of molecular techniques, including next-generation sequencing (NGS), was able to detect M. bovis DNA in the environment to investigate epidemiological questions. The aim of this study was, therefore, to apply a combination of culture-independent methods, such as targeted NGS (tNGS), to detect pathogenic mycobacteria, including M. bovis, in water sources located in a rural area of KwaZulu-Natal (KZN), South Africa. This area was selected based on the high burden of MTBC in human and animal populations. Water samples from 63 sites were screened for MTBC DNA by extracting DNA and performing hsp65 PCR amplification, followed by Sanger amplicon sequencing (SAS). Sequences were compared to the National Centre for Biotechnology Information (NCBI) database for genus or species-level identification. Samples confirmed to contain mycobacterial DNA underwent multiple PCRs (hsp65, rpoB, and MAC hsp65) and sequencing with Oxford Nanopore Technologies (ONT) tNGS. The ONT tNGS consensus sequences were compared to a curated in-house database to identify mycobacteria to genus, species, or species complex (e.g., MTBC) level for each sample site. Additional screening for MTBC DNA was performed using the GeneXpert® MTB/RIF Ultra (GXU) qPCR assay. Based on GXU, hsp65 SAS, and ONT tNGS results, MTBC DNA was present in 12 of the 63 sites. The presence of M. bovis DNA was confirmed at 4 of the 12 sites using downstream polymerase chain reaction (PCR)-based methods. However, further studies are required to determine if environmental M. bovis is viable. These results support further investigation into the role that shared water sources may play in TB epidemiology.